2001
DOI: 10.1016/s0022-2860(00)00829-2
|View full text |Cite
|
Sign up to set email alerts
|

The characterisation by luminescence spectroscopy of uranium(VI) incorporated into zeolites and aluminas

Abstract: Luminescence spectroscopy of solids at 77 K has been used to characterise the uranium(VI) species incorporated into a-alumina, g-alumina and zeolites Y and ZSM-20 by adsorption from solution and into ZSM-5 by chemical synthesis. With uranyl adsorbed from nitrate solutions onto a-and g-aluminas, the luminescence measurements show the dominant uranium species is schoepite, UO 3´x H 2 O, in agreement with results from X-ray diffraction and Raman spectroscopy. With uranyl acetate, there are indications that a crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The quenching of the luminescence of the Cu + by O 2 can be used to assess the distribution of Cu + in the zeolite . Other studies with UO 2 2+ have looked at energy transfer. , It was found that the efficiency of the energy transfer depended on the apparent dimensionality of the zeolite . For zeolite A with surface-bound UO 2 2+ , the transfer of energy to Eu 3+ was high at 93%, whereas UO 2 2+ on the inner surface of X and Y gave only an efficiency of energy transfer of 40%.…”
Section: 19 Luminescence Of Inorganic Molecules In Zeolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The quenching of the luminescence of the Cu + by O 2 can be used to assess the distribution of Cu + in the zeolite . Other studies with UO 2 2+ have looked at energy transfer. , It was found that the efficiency of the energy transfer depended on the apparent dimensionality of the zeolite . For zeolite A with surface-bound UO 2 2+ , the transfer of energy to Eu 3+ was high at 93%, whereas UO 2 2+ on the inner surface of X and Y gave only an efficiency of energy transfer of 40%.…”
Section: 19 Luminescence Of Inorganic Molecules In Zeolitesmentioning
confidence: 99%
“…Inorganic cations have been exchanged into zeolite and their emission characteristics used to comment on the zeolite. For Ag + in zeolites Y and X, the luminescence is similar to that of Ag + in rare gas matrices, and the spectrum shifts with the Si/Al ratio as a consequence of the charge density and polarizability of the Ag + environment. Cuprous ion (Cu + ) is readily produced from Cu 2+ adsorbed in zeolites.…”
Section: 19 Luminescence Of Inorganic Molecules In Zeolitesmentioning
confidence: 99%
“…47 Other U XAFS-based characterization studies that were designed to precipitate zeolites in the presence of micro M levels of U(VI) have been conducted. 48 These studies indicated that the U that precipitated during the formation of the zeolite (specifically, sodalite) was present in multiple forms such as uranyl oxide/oxide hydrates and silicates in addition to some uranate (as opposed to strictly uranyl) forms of U(VI).…”
Section: U(vi) Co-precipitate Formsmentioning
confidence: 99%
“…Although, the usability of Z and YZ in adsorption procedures have been proved with a number of investigations ( [8][9][10][11][12][13][14][15][16] for Z, and [17][18][19][20][21][22][23] for Y-zeolite), further researches require for enhancement of adsorptive features and practical usage of zeolites, since the aggregation and coagulation of mineral particles under varying conditions of temperature and electrolytes lead variations in flow properties of these minerals. This is an undesired feature for their practical use as adsorbents since it may result in e.g.…”
Section: Introductionmentioning
confidence: 99%